The Philosophy of Forestry - Erickson, Glenn W. (Princípios: Revista de Filosofia (UFRN), 2010)
Abstrac: In an extended discussion, within the context of a"philosophy offorestry", of the relationships of the concepts of truth and of tree some fundamental aspects of occidental metaphysics are examined from a Heideggerian perspective. But the paper tries to go beyond Heidegger's thematization of metaphysics in the context of pre-Socratic philosophy by establishing Indo-European etymology as a more inclusive horizon. In this manner, the transition from anti-metaphysics to post-metaphysics is anticipated.